Young Children's Healthcare in Samara Region in 1918-1940 Years - Roman S. Serebryaniy; Oksana V. Yaremchuk; Stella A. Sher (Вопросы современной педиатрии)
The article is devoted to the young children’s healthcare in Samara region in the period from 1918 to 1940. The aim of the study was to demonstrate the evolution of healthcare system for children of the first three years of life in Samara-Kuibyshev region in the 1920-1930s (according to archival and literary sources). The results of historical and medical research have shown that children's healthcare in Samara-Kuibyshev region during this time period achieved significant success in implementation of urban and rural children's institutions (children’s health centers, nurseries, infant-feeding centers). Human resources increased significantly, medical staff qualification improved. All that together led to enhancement of children primary care, children and infants mortality decrease. At the same time, the performed analysis has revealed the crucial problems of children's healthcare in Samara. Archival materials from Samara region characterize the situation with children's healthcare in the country in general during the tragic years of famine (1921-1922 and 1932-1933). These years were accompanied by increase of children morbidity and mortality. Statistics has shown that the areas affected by famine had natural decline in the population even in 1937. The results of this research of evolution of healthcare system for young children in Samara region during first two decades of Soviet Russia can be used in the educational process (history of pediatrics) of students in Samara medical colleges and universities, they can assist with creation of fundamental work on the history of children’s healthcare in the Soviet Union.